Method for surface treatment of low-activated ferrite / martensitic steel, surface modified low-activated ferrite / martensitic steel
By performing three-step surface treatment of low-activated ferrite/martensite steel, including surface nanoification, thermal aging and re-nanoization, the problem of its performance degradation in the high-temperature environment of nuclear fusion reactors is solved, and the mechanical properties and corrosion resistance are significantly improved.
Patent Information
- Application Number
- CN202411767751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Low-activated ferrite/martensite steel is prone to hardening and embrittlement in the high temperature environment of nuclear fusion reactors, resulting in a decline in material performance and also affecting material performance during welding processing.
A three-step surface treatment method is adopted: the first step is to perform surface nano-narcotic treatment on low-activated ferrite/martensite steel to form a nanocrystalline layer; the second step is to perform thermal aging treatment to promote the distribution of precipitated phases in the nanocrystalline layer; the third step is to perform surface nano-narcotic treatment again to further refine the grains in the nanocrystalline layer.
Through the above surface treatment method, the mechanical properties and corrosion resistance of RAFM steel are significantly improved, the performance decline of the material in high temperature environments is delayed, and the application reliability of its in nuclear fusion reactors is improved.
Smart Images

Figure CN119242901B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal material preparation, and in particular, to a method for surface treatment of low-activated ferrite / martensitic steel and surface-modified low-activated ferrite / martensitic steel. Background Art
[0002] As a clean energy, controlled nuclear fusion energy is one of the most important ways to solve the problem of future energy shortage and achieve sustainable development of human society, and it is also an important means to achieve energy conservation and emission reduction goals. Fusion energy is obtained by nuclear fusion, that is, two atomic nuclei with smaller mass combine to form a new nucleus with larger mass and release energy, such as deuterium-tritium fusion. Compared with the uranium-235 resources required for nuclear fission, the total amount of hydrogen isotope deuterium involved in nuclear fusion reactions is huge. Therefore, the development of nuclear fusion energy is one of the important means to solve the energy problem of mankind.
[0003] Reduced Activation Ferrite / Martensitic Steels (RAFM) is one of the candidate structural materials for nuclear fusion reactors, which must be able to serve safely in very harsh environments. RAFM has low radiation swelling and thermal expansion coefficients, high thermal conductivity, and has the potential to meet the structural material requirements of future fusion demonstration reactors and fusion power reactors.
[0004] Low-activated ferrite / martensitic steel is one of the candidate structural materials for nuclear fusion reactors. The ambient temperature of a nuclear fusion reactor is above 550°C. Under this condition, RAFM steel is easily induced to harden and embrittle by radiation, resulting in long-term thermal aging problems and reduced creep strength, affecting its material properties. In addition, during the welding process of RAFM steel, the welding heat generated by the welding process causes the material performance to deteriorate, such as the degradation of material performance in the heated area caused by pre-weld heat treatment and irradiation. This is also a technical challenge faced by RAFM steel in the application of controlled nuclear fusion technology. For example, the cladding structure material in the International Thermonuclear Experimental Reactor (ITER) project mainly uses RAFM steel, but how to process special-shaped parts and weld connections of RAFM steel is still a technical difficulty to be solved.
[0005] Surface nano-processing technology can generate a nano-crystalline layer of tens to hundreds of microns on the metal surface, thereby greatly improving the hardness and corrosion resistance of the metal without changing the composition and properties of the metal matrix. RAFM steel is treated with surface nano-processing technology to prepare a surface nano-crystalline layer on the surface of RAFM steel. However, in the working environment of a nuclear fusion reactor, continuous high temperature causes the grains in the nano-crystalline layer on the surface of RAFM steel to continue to grow, which can lead to a decrease in the high-temperature mechanical properties and thermal stability of the material. In order to meet the requirements for safe service in the harsh working environment of a nuclear fusion reactor, more research and development of RAFM steel is needed.
[0006] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0007] In a first aspect of the present application, the present application proposes a method for surface treatment of low-activated ferrite / martensitic steel, comprising:
[0008] S1: performing a first surface nano-processing on the low-activation ferrite / martensitic steel to obtain a nano-crystalline layer;
[0009] S2: performing thermal aging treatment on the nanocrystalline layer;
[0010] S3: performing a second surface nano-crystal treatment on the nano-crystal layer.
[0011] In some embodiments, the temperature of the heat aging treatment is 730° C.-800° C., and the time of the heat aging treatment is 90 min-120 min. Thus, the distribution of the precipitated phase in the nanocrystalline layer of the RAFM steel can be optimized.
[0012] In some embodiments, the first surface nano-processing includes a surface self-nano-processing, wherein the surface self-nano-processing includes a surface mechanical treatment. Thus, a nanocrystalline layer can be prepared on the surface of the RAFM steel, and the material advantages of the RAFM steel itself can be fully utilized.
[0013] In some embodiments, the second surface nano-processing includes a surface self-nano-processing, wherein the surface self-nano-processing includes a surface mechanical treatment. Thus, a nano-crystalline layer can be prepared on the surface of the material, and grain refinement in the nano-crystalline layer can be controlled.
[0014] In some embodiments, the surface mechanical treatment includes at least one of surface mechanical grinding treatment, surface mechanical milling treatment, surface ultrasonic rolling treatment, surface ultrasonic shot peening treatment, supersonic particle bombardment treatment, and laser shock strengthening treatment.
[0015] In some embodiments, the surface ultrasonic shot peening treatment time is 30s-90s, and the particle size of the surface ultrasonic shot peening treatment is 2mm-4mm. Thus, the thickness of the nanocrystalline layer and the size of the grains can be controlled.
[0016] In some embodiments, the method includes: before the first surface nano-sizing treatment, the low-activation ferrite / martensitic steel is subjected to a solid solution treatment, thereby reducing the influence of internal stress of the material.
[0017] In some embodiments, the temperature of the solid solution treatment is 950° C.-1150° C., and the time of the solid solution treatment is 30 min-120 min. Thus, the surface treated low-activated ferrite / martensitic steel has a better surface treatment effect.
[0018] In the second aspect of the present application, the present application proposes a surface modified low-activated ferrite / martensitic steel, comprising: a substrate, the substrate comprising low-activated ferrite / martensitic steel; a nanocrystalline layer, the nanocrystalline layer is located on the surface of the substrate, and the thickness of the nanocrystalline layer is 12μm-18μm.
[0019] In some embodiments, in the nanocrystalline layer, the Dv50 particle size of the grains is 6nm-20nm. When the particle size of the grains is within the aforementioned range, the grains can be organized to form a relatively dense nanocrystalline layer with more dislocations, which can inhibit the initiation of fatigue cracks. Therefore, the nanocrystalline layer can improve the fatigue life of the surface-modified low-activated ferrite / martensitic steel.
[0020] In some embodiments, the average surface hardness is 227 HV-259 HV. Thus, the surface-modified low-activated ferrite / martensitic steel has good mechanical strength.
[0021] The beneficial effects of the technical solution proposed in this application include at least:
[0022] The method for surface treatment of low-activated ferrite / martensite steel proposed in the present application forms a nanocrystalline layer on the surface of RAFM steel through a first surface nano-treatment, and generates a precipitate phase at the grain boundary in the nanocrystalline layer on the surface of RAFM steel through a thermal aging treatment. The precipitate phase at the grain boundary restricts the further growth of the grains, and then the second surface nano-treatment is performed to further refine the grains in the nanocrystalline layer, improve the stability of the nanocrystalline layer, and thus improve the mechanical properties and corrosion resistance of the RAFM steel.
[0023] The surface-modified low-activated ferrite / martensitic steel proposed in the present application comprises: a substrate, the substrate comprises low-activated ferrite / martensitic steel; a nanocrystalline layer, the nanocrystalline layer is located on the surface of the substrate, and the thickness of the nanocrystalline layer is 12 μm-18 μm. The substrate comprises low-activated ferrite / martensitic steel, and the nanocrystalline layer is prepared by the surface treatment method proposed in the present application, which improves the surface properties of the substrate, so that it has better mechanical properties and corrosion resistance, thereby improving the material properties of the overall surface-modified low-activated ferrite / martensitic steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] Figure 1 Surface morphologies of materials treated with SA and SA+T, ac: RAFM steel sample treated with SA; df: RAFM steel sample treated with SA+T;
[0026] Figure 2 This is a schematic diagram of measuring the thickness of a nanocrystalline layer by TEM observation in Example 1 of the present application;
[0027] Figure 3 The element content of the surface of the heat-treated sample measured by EDS in Example 1 of the present application, Figure a is the point element distribution, and Figures bd are element surface scans;
[0028] Figure 4 Figure 1 is an XRD test curve of RAFM steel samples with different surface treatments. Figure a is an XRD graph of a RAFM steel sample that has not been treated with surface nano-sizing. Figure b is an XRD graph of a RAFM steel sample that has been treated with a first surface nano-sizing and a second surface nano-sizing. Figure c is an XRD graph of a RAFM steel sample that has been treated with a first surface nano-sizing.
[0029] Figure 5 It is the average Vickers hardness of RAFM steel in Examples 1 to 3 of the present application and the corresponding Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0030] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0031] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0032] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0033] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0034] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0037] In a first aspect of the present application, the present application proposes a method for surface treatment of low-activated ferrite / martensitic steel, comprising:
[0038] S1: performing a first surface nano-processing on the low-activation ferrite / martensitic steel to obtain a nano-crystalline layer;
[0039] S2: performing thermal aging treatment on the nanocrystalline layer;
[0040] S3: performing a second surface nano-crystal treatment on the nano-crystal layer.
[0041] The first surface nano-treatment can change the metallographic structure of the RAFM steel surface, forming a nano-crystalline layer with a certain thickness on the surface. The relatively fine grains in the nano-crystalline layer improve the surface performance of the RAFM steel. It slows down the failure phenomenon that starts from the surface of the material, thereby slowing down the influence of external substances and temperature on the main body of the material and reducing the deterioration of material properties. The RAFM steel with a nano-crystalline layer is subjected to heat aging treatment to promote the precipitation of carbides in the RAFM steel as precipitation phases at the grain boundaries under controlled temperature conditions. Reference Figure 1 After heat aging treatment, the carbides precipitated along the grain boundaries are distributed in a network. The carbides affect the dislocation movement in the metallographic structure of the material, thereby limiting the change of the grains. The carbides precipitated at the grain boundaries include ,refer to Figure 3 and Table 1, the data in Table 1 are Figure 3 The element content (at.%) at the point marked in a, the carbide includes Cr, Mn and W. The carbide has a high hardness and produces a secondary hardening effect on the nanocrystalline layer. The nanocrystalline layer is then subjected to a second surface nano-processing to further refine the grains on the surface of the nanocrystalline layer. Figure 4 After the surface treatment method proposed in the present application, a surface nanostructured layer structure with more uniform grain size and more controllable grain size can be obtained. After the surface treatment method proposed in the present application, the RAFM steel has better mechanical properties and corrosion resistance.
[0042] Table 1
[0043]
[0044] In some embodiments, the temperature of the thermal aging treatment is 730°C-800°C, and the time of the thermal aging treatment is 90min-120min. Within the temperature range and time range of the aforementioned thermal aging treatment, the residual stress of the RAFM steel after the first surface nano-treatment can be effectively released. At the same time, the thermal effect of the thermal aging treatment affects the composition of the microstructure in the nanocrystalline layer of the RAFM steel, so that the precipitated phase precipitates at the grain boundary. As a result, the distribution of the precipitated phase in the nanocrystalline layer of the RAFM steel can be optimized.
[0045] In some embodiments, the first surface nano-processing includes a surface self-nano-processing, wherein the surface self-nano-processing includes a surface mechanical treatment. In the surface nano-processing, the material after the surface self-nano-processing does not change in chemical composition, but through repeated plastic deformation of the surface, a nano-crystalline layer with a certain thickness is formed from the surface to the inside of the material. The nano-crystalline layer has the characteristics of nano-gradient deformation, but still has the advantages of the RAFM steel material's own characteristics, such as: resistance to neutron irradiation, and its material mechanical properties and corrosion resistance are improved. Thus, a nano-crystalline layer can be prepared on the surface of RAFM steel, and the material advantages of RAFM steel itself can be fully utilized.
[0046] In some embodiments, the second surface nano-processing includes a surface self-nano-processing, wherein the surface self-nano-processing includes a surface mechanical process. In the surface self-nano-processing, the surface mechanical process repeatedly and strongly applies stress to the material surface, so that the material is repeatedly plastically deformed from the surface, thereby inducing changes in the microstructure, so that a nanocrystalline layer is formed and the grains therein are continuously refined. Thus, a nanocrystalline layer can be prepared on the material surface, and the grain refinement in the nanocrystalline layer can be controlled.
[0047] In some embodiments, the surface mechanical treatment includes at least one of surface mechanical grinding treatment, surface mechanical milling treatment, surface ultrasonic rolling treatment, surface ultrasonic shot peening treatment, supersonic particle bombardment treatment, and laser shock strengthening treatment.
[0048] In some embodiments, the surface ultrasonic shot peening treatment time is 30s-90s, and the shot particle size of the surface ultrasonic shot peening treatment is 2mm-4mm. When the shot particle size is within the aforementioned range, the strengthening thickness corresponding to the nanocrystalline layer can be achieved. When the shot peening treatment time is within the aforementioned range, the grain refinement of the nanocrystalline layer can better improve the surface hardness and strength of the RAFM steel. Thus, the thickness of the nanocrystalline layer and the size of the grains can be controlled.
[0049] As an example, the particle sizes of the shots subjected to the surface ultrasonic shot peening treatment are 2 mm, 2.5 mm, 3 mm, 3.5 mm, and 4 mm.
[0050] As an example, the surface ultrasonic shot peening treatment time is 30s, 35s, 40s, 45s, 50s, 55s, 60s, 65s, 70s, 75s, 80s, 85s, or 90s.
[0051] In some embodiments, the method includes: before the first surface nano-processing, the low-activated ferrite / martensitic steel is subjected to a solid solution treatment. The solid solution treatment is within a certain temperature and time range, so that the low-activated ferrite / martensitic steel is placed in a high temperature environment, and the unstable unbalanced structure in the low-activated ferrite / martensitic steel is gradually transformed into a stable balanced structure, the metallographic structure of the material is more uniform, and the internal stress of the material is reduced. Thus, the influence of the internal stress of the material can be reduced.
[0052] In some embodiments, the temperature of the solution treatment is 950°C-1150°C, and the time of the solution treatment is 30min-120min. The solution treatment within the aforementioned temperature range and time range can effectively eliminate the residual stress in the material and adjust the metallographic structure in the material. This is conducive to a better surface treatment effect of the surface-treated low-activated ferrite / martensitic steel.
[0053] In the second aspect of the present application, the present application proposes a surface modified low-activated ferrite / martensitic steel, comprising: a substrate, the substrate comprising low-activated ferrite / martensitic steel; a nanocrystalline layer, the nanocrystalline layer is located on the surface of the substrate, and the thickness of the nanocrystalline layer is 12μm-18μm.
[0054] The matrix comprises a low activated ferrite / martensitic steel. Figure 2 The nanocrystalline layer is prepared by the surface treatment method proposed in this application, which improves the surface properties of the substrate and makes it have better mechanical properties and corrosion resistance, thereby improving the material properties of the overall surface modified low-activated ferrite / martensitic steel.
[0055] In some embodiments, in the nanocrystalline layer, the Dv50 particle size of the grains is 6nm-20nm. When the particle size of the grains is within the aforementioned range, the grains can be organized to form a relatively dense nanocrystalline layer with more dislocations, which can inhibit the initiation of fatigue cracks. Therefore, the nanocrystalline layer can improve the fatigue life of the surface-modified low-activated ferrite / martensitic steel.
[0056] In some embodiments, the average surface hardness is 227 HV-259 HV. Thus, the surface-modified low-activated ferrite / martensitic steel has good mechanical strength.
[0057] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0058] Example 1
[0059] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 950 °C for 45 min.
[0060] First surface ultrasonic shot peening surface nano-treatment (U): The sample after solution treatment was polished to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm, and the surface ultrasonic shot peening treatment time was 1 minute.
[0061] Thermal aging treatment (T): The RAFM steel sample that had undergone the first surface ultrasonic shot peening surface nano-treatment was thermally aged at 760°C for 90 minutes to precipitate carbides at the grain boundaries.
[0062] Second surface ultrasonic shot peening surface nano-treatment (U): The sample after heat aging treatment was sanded to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm, and the surface ultrasonic shot peening treatment time was 1 minute.
[0063] Comparative Example 1
[0064] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 950 °C for 45 min.
[0065] Thermal aging treatment (T): The RAFM steel sample after solution treatment was thermally aged at 760 °C for 90 min to precipitate carbides at the grain boundaries.
[0066] Ultrasonic shot peening surface nano-treatment (U): The samples after heat aging treatment were sanded to 3000# with sandpaper and surface nano-treatment was performed using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm and the surface ultrasonic shot peening treatment time was 1 min.
[0067] Example 2
[0068] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 980 °C for 45 min.
[0069] First surface ultrasonic shot peening surface nano-treatment (U): The sample after solution treatment was polished to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 3 mm, and the surface ultrasonic shot peening treatment time was 1 minute.
[0070] Thermal aging treatment (T): The RAFM steel sample that had undergone the first surface ultrasonic shot peening surface nano-treatment was thermally aged at 760°C for 90 minutes to precipitate carbides at the grain boundaries.
[0071] Second surface ultrasonic shot peening surface nano-treatment (U): The sample after heat aging treatment was sanded to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 3 mm, and the surface ultrasonic shot peening treatment time was 1 minute.
[0072] Comparative Example 2
[0073] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 980 °C for 45 min.
[0074] Thermal aging treatment (T): The RAFM steel sample after solution treatment was thermally aged at 760 °C for 90 min to precipitate carbides at the grain boundaries.
[0075] Ultrasonic shot peening surface nano-treatment (U): The samples after heat aging treatment were sanded to 3000# with sandpaper and surface nano-treatment was performed using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 3 mm and the surface ultrasonic shot peening treatment time was 1 min.
[0076] Example 3
[0077] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 1000 °C for 30 min.
[0078] First surface ultrasonic shot peening surface nano-treatment (U): The sample after solution treatment was polished to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm, and the surface ultrasonic shot peening treatment time was 30 seconds.
[0079] Thermal aging treatment (T): The RAFM steel sample that had undergone the first surface ultrasonic shot peening surface nano-treatment was thermally aged at 760°C for 90 minutes to precipitate carbides at the grain boundaries.
[0080] Second surface ultrasonic shot peening surface nano-treatment (U): The sample after heat aging treatment was sanded to 3000# with sandpaper, and the surface was nano-treated using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm, and the surface ultrasonic shot peening treatment time was 30 seconds.
[0081] Comparative Example 3
[0082] Solution treatment (SA): RAFM steel block samples with a size of 10 mm × 10 mm × 3 mm were treated at 950 °C for 45 min.
[0083] Thermal aging treatment (T): The RAFM steel sample after solution treatment was thermally aged at 760 °C for 90 min to precipitate carbides at the grain boundaries.
[0084] Ultrasonic shot peening surface nano-treatment (U): The samples after heat aging treatment were sanded to 3000# with sandpaper and surface nano-treatment was performed using a SONIC JY-P20 ultrasonic shot peening machine. The particle size of the shot peening was 2 mm and the surface ultrasonic shot peening treatment time was 30 seconds.
[0085] Test method:
[0086] 1. Thermal stability evaluation: The RAFM steel sample that has undergone two surface nano-treatments and thermal aging treatments was heat treated in a vacuum high temperature environment (A) to observe its thermal stability. The sample was placed in a quartz tube and vacuum sealed to prevent oxidation of the sample surface. The sealed quartz tube was placed in a heat treatment furnace for heat treatment. The heat treatment temperature was 650°C and the holding time was 24 hours.
[0087] 2. Grain size measurement: The grain size of RAFM steel was measured by XRD technology to evaluate its thermal stability. During the XRD test, continuous scanning was performed from 20°-90° at a scanning rate of 6° / min. The grain size of the sample was calculated using the Scherrer-Wilson formula, and the three main peaks (110), (200), and (211) were selected for fitting calculation.
[0088] 3. Hardness test: The Vickers hardness of the sample surface was measured by HVS-1000 Vickers hardness tester. The loading force used was 0.01 kg and the loading time was 15 s. Three locations on each sample surface were tested and the average value was calculated.
[0089] 4. Nanocrystalline layer thickness test: Prepare the cross section of the sample after surface treatment, observe the thickness of the nanocrystalline layer of the sample by transmission electron microscopy (TEM), and calculate its average value.
[0090] Test results:
[0091] Grain size and nanocrystalline layer thickness test results: see Table 2
[0092] Table 2
[0093]
[0094] Thermal stability evaluation test results: see Table 3
[0095] Table 3
[0096]
[0097] As shown in Table 2, compared with the corresponding comparative examples 1 to 3, the average thickness of the nanocrystalline layer on the surface of RAFM steel prepared by the surface treatment method proposed in this application is improved, and the average grain size in the nanocrystalline layer is reduced. This shows that the surface treatment method proposed in this application can better control the grain size of the nanocrystalline layer, so that the nanocrystalline layer has a more dense structure. Figure 5 Compared with the corresponding comparative examples 1 to 3, the Vickers hardness of the materials in Examples 1 to 3 is improved.
[0098] As can be seen from Table 3, the test results of thermal stability evaluation show that the average grain size of Examples 1 to 3 is relatively small compared with the corresponding Comparative Examples 1 to 3. After continuous high temperature, the growth of grains in the surface nanocrystalline layer of the RAFM steel treated by the surface treatment method proposed in this application is still subject to certain constraints. This shows that the nanocrystalline layer with a more stable structure is prepared by the surface treatment method proposed in this application, and the growth of grains in the nanocrystalline layer is subject to certain restrictions, thereby improving the mechanical properties and corrosion resistance of the material.
[0099] In the description of the present application, it should be understood that the terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0100] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0101] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0102] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0103] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for surface treatment of low-activated ferrite / martensitic steel, characterized in that: include: S1: performing a first surface nano-processing on the low-activation ferrite / martensitic steel to obtain a nano-crystalline layer; S2: performing thermal aging treatment on the nanocrystalline layer; S3: performing a second surface nano-processing on the nano-crystalline layer, The temperature of the heat aging treatment is 730° C.-800° C., and the time of the heat aging treatment is 90 min-120 min.
2. The method for surface treatment of low-activated ferrite / martensitic steel according to claim 1, characterized in that: The first surface nano-processing includes surface self-nano-processing, wherein the surface self-nano-processing includes surface mechanical processing; and / or, The second surface nano-processing includes surface self-nano-processing, wherein the surface self-nano-processing includes surface mechanical processing.
3. The method for surface treatment of low-activated ferrite / martensitic steel according to claim 2, characterized in that: The surface mechanical treatment includes at least one of surface mechanical grinding treatment, surface mechanical milling treatment, surface ultrasonic rolling treatment, surface ultrasonic shot peening treatment, supersonic particle bombardment treatment, and laser shock strengthening treatment.
4. The method for surface treatment of low-activated ferrite / martensitic steel according to claim 3, characterized in that: The time of the surface ultrasonic shot peening treatment is 30s-90s, and the particle size of the shot peening treatment is 2mm-4mm.
5. The method for surface treatment of low-activated ferrite / martensitic steel according to any one of claims 1 to 4, characterized in that: include: Before the first surface nano-sizing treatment, the low-activation ferrite / martensite steel is subjected to a solid solution treatment.
6. The method for surface treatment of low-activated ferrite / martensitic steel according to claim 5, characterized in that: The temperature of the solution treatment is 950° C.-1150° C., and the time of the solution treatment is 30 min-120 min.
7. A surface modified low-activated ferrite / martensitic steel, characterized in that: The low-activated ferrite / martensitic steel is prepared by the surface treatment method of any one of claims 1 to 6, wherein the low-activated ferrite / martensitic steel comprises: a substrate comprising a low-activation ferrite / martensitic steel; A nanocrystalline layer, wherein the nanocrystalline layer is located on the surface of the substrate, and the thickness of the nanocrystalline layer is 12 μm-18 μm.
8. The surface modified low-activated ferrite / martensitic steel according to claim 7, characterized in that: In the nanocrystalline layer, the Dv50 particle size of the grains is 6nm-20nm.
9. The surface modified low-activated ferrite / martensitic steel according to claim 7, characterized in that: The average surface hardness is 227HV-259HV.
Citation Information
Patent Citations
Method for preparing nanocrystalline metal material containing nano-sized precipitates within crystal
CN104726803A
Ultrasonic shot peening treatment method and device integrating surface nanocrystallization and polishing and grinding
CN115652049A